COMMUNITY COMMUNITY EMPOWERMENT PROCESSING GEDEBOG BANANA WASTE INTO "BANANA THE BOG" IN KRANDON TEGAL DISTRICT - Dewi Amaliah Nafiati, Dewi Amaliah Nafiati; Hendaryati, Neni; Nurfariza, Ananda Sabilla; Maghfiroh, Nizma Laela; Fitriani, Syakila Rahma; Arofah, Zulfi (Perwira Journal of Community Development, 2025)
Community service activities are carried out to foster creativity in processing organic waste which is often found in the community. Banana gedebog waste is often found and its processing has not been utilized optimally. Gedebog bananas have quite high nutritional and fiber content which can help the immune system and human health if processed properly. After harvesting bananas, banana gedebogs often pile up and become waste, whereas overseas the price turns out to be very high. This community service aims to: 1) Provide counseling and assistance so that participants have knowledge about the benefits of banana gedebog waste and stimulate participants' creativity in processing banana gedebog into alternative food that has good nutrition. 2) Accompany participants to practice how to process banana gedebog into snacks in the form of banana gedebog chips. 3) The assistance process is carried out from the beginning of the processing process to the packaging process so that it can be sold. 4) Assist in creating an online sales platform on social media. Community service activities are carried out in groups of PKK women in Krandon Village, Margadana District, Tegal City according to mutually agreed times so that the empowerment goals can be achieved.